Cuticular wax metabolism responses to atmospheric water stress on the exocarp surface of litchi fruit after harvest. (15th July 2023) - Huang, Hua; Liu, Hailun; Wang, Ling; Xiang, Xu
Highlights: Rapid water loss together with pericarp browning occurred at water deficit atmospheres. VLC fatty acids, primary alcohols, and n -alkanes changed mostly following water loss. Biosynthesis of VLC waxes was modified following water loss and pericarp browning. Cuticular wax metabolism altered in response to both water loss and browning in litchi. Abstract: Litchi fruit is susceptible to pericarp browning, which is largely due to the oxidation of phenols in pericarp. However, the response of cuticular waxes to water loss of litchi after harvest is less mentioned. In this study, litchi fruits were stored under ambient, dry, water-sufficient, and packing conditions, while rapid pericarp browning and water loss from the pericarp were observed under the water-deficient conditions. The coverage of cuticular waxes on the fruit surface increased following the development of pericarp browning, during which quantities of very-long-chain (VLC) fatty acids, primary alcohols, and n -alkanes changed significantly. Genes involved in the metabolism of such compounds were upregulated, including LcLACS2, LcKCS1, LcKCR1, LcHACD, and LcECR for elongation of fatty acids, LcCER1 and LcWAX2 for n- alkanes, and LcCER4 for primary alcohols. These findings reveal that cuticular wax metabolism may take part in the response of litchi to water-deficient and pericarp browning during storage.